2008
DOI: 10.1051/0004-6361:20079182
|View full text |Cite
|
Sign up to set email alerts
|

Sub-hour modulation of L-component of Io-related Jovian decametric emission

Abstract: The variability of Jovian decametric emission (DAM) is studied at time scales from 1 min to 1 h with DAM records of 1991-2007 from the archive of Nancay Radio Observatory. We found that the internal structure of the Io-related radio storms has the dominating periodicity of 23±2 min on average. This estimate practically coincides with the fundamental eigenoscillations of transversal magnetic pulsations in the Io plasma torus. Our autocorrelation analysis confirms the excess of DAM variations with the time scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…These results and histograms ( Fig. 5 and 6) for non-Io emission are approximate to the modulation of Io-related DAM (Arkhypov & Rucker 2008). The simplest interpretation of these agreements is the identity of the modulator.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…These results and histograms ( Fig. 5 and 6) for non-Io emission are approximate to the modulation of Io-related DAM (Arkhypov & Rucker 2008). The simplest interpretation of these agreements is the identity of the modulator.…”
Section: Discussionsupporting
confidence: 65%
“…This estimate is about the average period of Io-related emission: P = 1403 ± 102 s or 23 ± 2 min (Arkhypov & Rucker 2008). For toroidal (transverse) magnetic oscillations in the Io torus, Glassmeier et al (1989) found theoretically the fundamental period of 1296 s (marked as F0 in Fig.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations